083 Facial twitching, breathlessness and fever: an unexpected and potentially lethal triad. Issue 12 (14th November 2019) - Mbizvo, Gashirai K; Lentell, Isabel; Leen, Clifford; Roddie, Huw; Derry, Chris; Duncan, Susan; Rannikmäe, Kristiina
Abstract : Background: We describe a patient co-presenting with epilepsia partialis continua (EPC), disseminated tuberculosis (TB), and hemophagocytic lymphohistiocytosis (HLH). Case: A 54-year-old lady presented with facial twitching, breathlessness, and night sweats. Clinical examination revealed pyrexia and continuous, stereotyped, right-sided facial contractions. These worsened with speech and continued through sleep. A clinical diagnosis of EPC was made (video provided). CT imaging of the chest and serous fluid analyses were consistent with a diagnosis of disseminated Mycobacterium tuberculosis, with a left motor strip tuberculoma evident on post-contrast MRI brain. An additional diagnosis of HLH was made following the identification of pancytopenia and hyperferritinaemia on peripheral blood, with hemophagocytosis evident on bone marrow investigation (pathology slides provided). She was extremely unwell and hospitalised for six months, including two admissions to intensive care for invasive ventilation. She was treated successfully with high doses of antiepileptic drugs, 12 months of oral anti-TB therapy, and chemotherapy with eight weeks of etoposide and dexamethasone for HLH, followed by 12 months of ciclosporin and prednisolone. Conclusions: Presentation with this triad is rare – to our knowledge, this is the first documented case. A lack of evidence surrounding the co-expression of this triad may represent absolute rarity or, more likely, clinical failure to recognise the triad (resulting in early death from untreated TB/HLH). Therefore, the case helps improve education around how such a patient may present and be managed.